Mammalian SWI/SNF Chromatin Remodeling Complexes in Embryonic Stem Cells: Regulating the Balance Between Pluripotency and Differentiation - Ye, Ying; Chen, Xi; Zhang, Wensheng (Frontiers in Cell and Developmental Biology, 2021)
The unique capability of embryonic stem cells (ESCs）to maintain and adjust the equilibrium between self-renewal and multi-lineage cellular differentiation contributes indispensably to the integrity of all developmental processes, leading to the advent of an organism in its adult form. The ESC fate decision to favor self-renewal or differentiation into specific cellular lineages largely depends on transcriptome modulations through gene expression regulations. Chromatin remodeling complexes play instrumental roles to promote chromatin structural changes resulting in gene expression changes that are key to the ESC fate choices governing the equilibrium between pluripotency and differentiation. BAF (Brg/Brahma-associated factors) or mammalian SWI/SNF complexes employ energy generated by ATP hydrolysis to change chromatin states, thereby governing the accessibility of transcriptional regulators that ultimately affect transcriptome and cell fate. Interestingly, the requirement of BAF complex in self-renewal and differentiation of ESCs has been recently shown by genetic studies through gene expression modulations of various BAF components in ESCs, although the precise molecular mechanisms by which BAF complex influence ESC fate choice remain largely underexplored. This review surveys these recent progresses of BAF complex on ESC functions, with a focus on its role of conditioning the pluripotency and differentiation balance of ESCs. A discussion of the mechanistic bases underlying the genetic requirements for BAF in ESC biology as well as the outcomes of its interplays with key transcription factors or other chromatin remodelers in ESCs will be highlighted.